2009 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition 2009
DOI: 10.1109/date.2009.5090665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating UML2 modeling of IP-XACT objects for automatic MP-SoC integration onto FPGA

Abstract: Abstract-IP-XACT is a standard for describing intellectual property metadata for System-on-Chip (SoC) integration. Recently researchers have proposed visualizing and abstracting IP-XACT objects using structural UML2 model elements and diagrams. Despite the number of proposals at conceptual level, experiences on utilizing this representation in practical SoC development environments are very limited. This paper presents how UML2 models of IP-XACT features can be utilized to efficiently design and implement a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Tools are used to process metadata and automatically generate final executable and configurations. Automation reduces design errors and offers speedup, especially when combined with graphical user interface [7], [9], [10]. III.…”
Section: B Ip Formulation For Reusementioning
confidence: 99%
“…Tools are used to process metadata and automatically generate final executable and configurations. Automation reduces design errors and offers speedup, especially when combined with graphical user interface [7], [9], [10]. III.…”
Section: B Ip Formulation For Reusementioning
confidence: 99%
“…The resulting IP-XACT design flow using UML is also presented which allows automatic RTL component integration based on the proposed transformation rules. Subsequently, the authors further demonstrated their approach in [27], adding modelling concepts, to implement a complex MP-SoC.…”
Section: Hardware Modeling Using Uml and Ip-xactmentioning
confidence: 99%